Efficacy of Angio-Seal Device for Primary And Complicated Haemostasis: a Multicentre Retrospective Assay - I. N. Sorokin; E. B. Shakhov; V. S. Zakharov; D. A. Savenkov; S. A. Ayvazyan; A. A. Frolov (Креативная хирургия и онкология, 2020)
Background. Femoral approach in endovascular surgery remains relevant being, however, associated with the risk of fatal and nonfatal complications. Modern techniques for instrumental haemostasis achieved with the AngioSeal device (Terumo Corporation, Japan) provide an opportunity to reduce the number of fatal and nonfatal complications. Aim. A multicentre assay of the efficacy and safety of instrumental puncture closure using AngioSeal devices (Terumo Corporation, Japan) in various settings and clinical situations.Materials and methods. A multicentre retrospective analysis of 1088 use cases of the AngioSeal device  (Terumo Corporation, Japan) for “primary” and “complicated” instrumental haemostasis after femoral access  has been conducted for the years 2018–2020. The mean patient age was 62.3 ± 11.6 years, including 845 men (78.0%) and 243 women (22.0%). Five centres for routine and emergency endovascular radiology participated in the study.Results. The AngioSeal device (Terumo Corporation, Japan) demonstrated a high method efficiency, with a  97.0% success rate of “primary” instrumental haemostasis (1055 of 1088 total successful haemostatic  procedures) in various clinical settings. Arterial thrombosis at the approach side had a 3.0% complication rate  (5 of 33 observations), all other complication types associated with haemorrhagic events (8 cases) or device malfunction and damage (20 cases).Discussion. The assay conducted suggests that the incidence of “complicated” instrumental haemostasis  relates to technical drawbacks of the device application that required advance planning. The key identified  prerequisites for a successful AngioSeal application (Terumo Corporation, Japan) are the alignment of anchor tubedelivery through soft tissue into the vessel lumen and its positioning inside the vessel.Conclusion. The constructive features and instrumental haemostatic technique realised in the AngioSeal  device (Terumo Corporation, Japan) enable an effective and safe primary sealing of arterial puncture site in 97% cases.